2021
DOI: 10.3390/mi12080982
|View full text |Cite
|
Sign up to set email alerts
|

Levitation Characteristics Analysis of a Diamagnetically Stabilized Levitation Structure

Abstract: A diamagnetically stabilized levitation structure is composed of a floating magnet, diamagnetic material, and a lifting magnet. The floating magnet is freely levitated between two diamagnetic plates without any external energy input. In this paper, the levitation characteristics of a floating magnet were firstly studied through simulation. Three different levitation states were found by adjusting the gap between the two diamagnetic plates, namely symmetric monostable levitation, bistable levitation, and asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Compared with the old structure [ 28 ], the push–pull diamagnetic levitation structure only introduces a pulling magnet, but has the advantages of multiple levitation equilibrium points, multiple maximum monostable levitation spaces, a large increase in horizontal recovery force, and more stable axial force distribution. The airflow energy harvester with the push–pull diamagnetic levitation structure has better output performance and a wider application range.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Compared with the old structure [ 28 ], the push–pull diamagnetic levitation structure only introduces a pulling magnet, but has the advantages of multiple levitation equilibrium points, multiple maximum monostable levitation spaces, a large increase in horizontal recovery force, and more stable axial force distribution. The airflow energy harvester with the push–pull diamagnetic levitation structure has better output performance and a wider application range.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The DSMLG is based on the stable levitation properties of a structure developed [ 62 ] through the investigation of the levitation properties of the floating magnet within a diamagnetically stabilized levitation system. The floating magnet in the diamagnetically stabilized levitation structure exhibits three distinct levitation states—symmetric monostable levitation, bistable levitation, and asymmetric monostable levitation—with our main focus on the symmetric monostable levitation mode [ 63 ]. This study presents the results of simulations to explore the levitation characteristics of the structure, and in particular, the effect of adjusting the gap between diamagnets and magnets on the resulting magnetic spring Hooke’s Law constant.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (27) reported a low-frequency wideband piecewise linear EVEH based on the diamagnetic levitation mechanism, in which a floating magnet impacts an elastic film at the edge under low-frequency horizontal vibration excitation. Cheng et al (28) designed a monostable diamagnetic levitation EVEH using the Taguchi method, which generated an RMS voltage of 250.69 mV and a power of 86.8 μW under 2.6 Hz vibration excitation.…”
Section: Introductionmentioning
confidence: 99%